PUJIAN DALAM BAHASA INGGRIS DAN BAHASA TONTEMBOAN (SUATU ANALISIS KONTRASTIF) - Tenda, Patriceila Syanetha; Lasut, Theresia M. C.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThisÂ  researchÂ  isÂ  entitledÂ  â€œPujian dalam Bahasa Inggris dan Bahasa Tontemboan (Suatu Analisis Kontrastif).â€ The objectives of this research are to classify, to identify, and to describe the topic of compliments and compliment responses in English and Tontemboan language, and also to analyze the similarities and the differences of the complimentsÂ  and compliment responses in both languages. This research uses a descriptive method. The data of compliments and compliment responses in English language were collected from novel, films, and journals, while the data in Tontemboan language were collected from the informants of native speaker by doing observation. The data that have been collected then analyze by using the theory of Wolfson in Richard and Schmidt (1986) and theory of Richard and Schmidt (1986), and then the writer uses the theory of Lado (1957) to make a contrastive analysis in finding out the similarities and the differences of English and Tontemboan language. The result shows that the topic of compliments in English consists of personal attribute, possession, children, pet, accomplishment, and change in appearance, and the topic of compliments in Tontemboan consists of personal attribute, possession, children, pet, accomplishment, and change in appearance. The compliment responses in English are acceptance, agreement, rejection, shift, and return, and the compliment responses in Tontemboan are acceptance, agreement, rejection, shift, and return. The similarities of the topics of compliment in English and Tontemboan which are found namely personal attribute, possession, children, pet, accomplishment, and change in appearance, and the compliment responses in English and Tontemboan namely acceptance, agreement, rejection, shift, and return. The difference of both languages namely the topics of compliment in Tontemboan is found about food, while English language hasnâ€™t. The response of compliments in English is found high fives, while in Tontemboan are found smile and laugh. The adjectival words which are used in English compliments namely beautiful, great, good, great, lucky, special, smarter, intelligent, charming, kind, nice, bright, cherry, best, grown up, amazing, incredible, very good, well, prefect, and awesome, while in Tontemboan namely keter, teâ€™es, jagoâ€™, kagagah, keli, weru, wangker, kemel, kaloâ€™or, papasungan, mantap, bos, wangkoâ€™,Â  dan rangkaâ€™. The verbal words used in English compliments namely like and love, and in Tontemboan language namely malekepâ€™o, makeilekâ€™o, and aweano. The adjectival used frequently in English are beautiful, great, and good, and in Tontemboan namely gagah, numanam, and wangker. Â Keywords: Compliments, English and Tontemboan Language, Contrastive Analysis.